Urgensi Perlindungan Sosial dalam Upaya Pemenuhan Hak-Hak Anak Yatim Piatu Korban Pandemi Covid-19 - Retnaningsih, Hartini (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2021)
The Covid-19 pandemic has affected the welfare of Indonesian children. Many children have suddenly become orphans due to the death of their parents due to the Covid-19. These children need help to be able to continue life after the death of their parents. This paper examines social protection in an effort to fulfill the rights of orphans victims of the Covid-19 pandemic. The writing method is a documentary study using the theory/concept of social protection as an analytical tool. The results of the study show that social protection is very important in order to fulfill the rights of orphans victims of the Covid-19 pandemic. They are vulnerable children whoneed serious treatment after the death of their parents. Social protection in this case is not just a humanitarian action but is more aimed at saving the future of the next generations who are expected to become useful people for the nation and state. These orphans are a big issue that must be overcome. Social protection should be carried out systematically and comprehensively, taking into account the following steps: (1) identifying the problems of orphans victims of the Covid-19 pandemic; (2) listening to the opinions of orphans victims of the Covid-19 pandemic; (3) assessment and analysis of issues to be addressed; (4) budget allocation and fundraising; and (5) social protection measures in an effort to fulfill the rights of orphans victims of the Covid-19 pandemic. The recommendations are: (1) the government immediately completes data collection for orphans victims of the Covid-19 pandemic; (2) the government prepares social protection measures for orphans victims of the Covid-19 pandemic; (3) the Indonesian House of Representatives keep monitoring the government's performance regarding the implementation of social protection for orphans victims of the Covid-19 pandemic.AbstrakPandemi Covid-19 telah memengaruhi kesejahteraan anak Indonesia. Banyak anak mendadak menjadi yatim piatu karena kematian orang tua akibat Covid-19. Anak tersebut memerlukan bantuan untuk dapat melanjutkan kehidupan setelah kematian orang tuanya. Tulisan ini mengkaji tentang perlindungan sosial dalam upaya pemenuhan hak-hak anak yatim piatu korban pandemi Covid-19. Tulisan ini menggunakan studi dokumentasi dengan teori/konsep perlindungan sosial sebagai alat analisis. Hasil kajian menunjukkan bahwa perlindungan sosial sangat penting dilakukan dalam rangka pemenuhan hak-hak anak yatim piatu korban pandemi Covid-19. Mereka adalah anak rentan yang membutuhkan penanganan serius setelah kematian orang tuanya. Perlindungan sosial dalam hal ini bukan sekadar tindakan kemanusiaan, namun lebih ditujukan pada upaya penyelamatan masa depan generasi penerus yang diharapkan kelak menjadi orang yang berguna bagi bangsa dan negara. Anak yatim piatu tersebut merupakan isu besar yang harus diatasi. Perlindungan sosial seharusnya dilakukan secara sistematis dan komprehensif, dengan memperhatikan langkah-langkah sebagai berikut: (1) identifikasi masalah anak yatim piatu korban pandemi Covid-19; (2) dengar pendapat anak yatim piatu korban pandemi Covid-19; (3) asesmen dan analisis isu-isu yang harus ditangani; (4) alokasi anggaran dan penggalian dana; dan (5) tindakan perlindungan sosial dalam upaya pemenuhan hak-hak anak yatim piatu korban pandemi Covid-19. Rekomendasi yang dikemukakan: (1) pemerintah segera menuntaskan pendataan anak yatim piatu korban pandemi Covid-19; (2) pemerintah menyiapkan langkah-langkah perlindungan sosial bagi anak yatim piatu korban pandemi Covid-19; dan (3) DPR RI terus melakukan pengawasanterhadap kinerja pemerintah terkait penyelenggaraan perlindungan sosial bagi anak yatim piatu korban pandemi Covid-19.